Losartan in combination with propranolol slows the aortic root dilatation in neonatal Marfan syndrome - Lu-Hang Liu; Shan-Miao Lin; Dar-Shong Lin; Ming-Ren Chen (Elsevier, 2018)
Neonatal Marfan syndrome, in contrast to classical Marfan syndrome, is characterized by rapidly progressive multi-valvular cardiac disease and death from congestive heart failure, typically within the first year of life. Due to the rarity of this condition, treatment for neonatal Marfan syndrome has not been well studied. In this report, a combination of losartan and propranolol reduced the aortic root dilatation rate after three months of losartan therapy. Genetic analysis in this patient revealed a mutation in exon 25 of the FBN1 gene, which typically results in a shorter life expectancy. However, the patient's heart failure was controlled by losartan, propranolol and other anti-congestive medications, which may have prolonged his survival. Key Words: FBN1, losartan, neonatal Marfan syndrome